A study on labour welfare towards complying to labour welfare policies in Felda (Jengka) oil palm plantation / Mohamad Arizzudin Romli - Romli, Mohamad Arizzudin (Faculty of Plantation and Agrotechnology, 2016)
Majority oil palm plantation in Malaysia uses foreign labours as harvester, pruner, and general workers. Therefore foreign labour welfare are important to protect their right in plantation. The objectives ofthe study are: (a) to examine the welfare of the labours (living condition, and working condition). (b) to study the medical care management of the labours. (c) To identifY the relationship between selected demographic characteristic, and welfare towards complying to labours welfare policies. This study is in form of survey, using one instrument for data collection i.e. Questionnaire. In obtaining primary result, 150 respondents was choose randomly in this study and distributes 150 questionnaires to respondents. The data was analyses using descriptive analysis, correlation and multiple regression technique. The results shows medical care management has significant with moderate relationship towards complying to labour welfare policies, while living condition and working condition also have significant but low relationship towards complying to labour welfare policies. Multiple linear regression showed the dominant elements towards complying to labour welfare policy in oil palm plantation. When the independent variable increases, the dependent will predict increase.